Traffic model for the interconnection of networks and operators using MPLS-TE - Restrepo, Carlos Mario; Salcedo-Parra, Octavio José; Sánchez-Céspedes, Juan Manuel (Universidad Pedagógica y Tecnológica de Colombia, 2017)
In this paper, the main features of MPLS Traffic Engineering are presented to illustrate how telecommunication service providers use them to create interconnections between each other in order to offer telecom services satisfying QoS commitments. Based on previous traffic models, a new model, which deals with traffic queue balancing for different Classes of Service, and for a provider using another provider´s network is presented. The model output shows that carrying another operator’s traffic may increase delays in an undesirable manner, forcing the carrier to increase the serving rate of LSRs until Utilization is below 60 %. In order to validate the model, a number of network scenarios are implemented in the Wolfram Mathematica 10.1 Study Version, based on study case configurations of an MPLS network. The total global model is useful for future implementation of test-beds of interconnected providers under an MPLS environment.